Pengaruh Reputasi Auditor, Investment Opportunities Set dan Kompleksitas Operasi Perusahaan Terhadap Audit Report Lag - Aisyah Sinta Balqis; Erinos NR (Universitas Negeri Padang, 2023)
This research is a quantitative research that aims to find out empirically the effect of auditor reputation, investment opportunity set and the complexity of company operations on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The samples collected were 261 data based on purposive sampling technique. The type of data used is secondary data obtained from www.idx.co.id or company website and other sites related to this research. The research data were analyzed using multiple linear regression analysis. Based on statistical analysis, it can be concluded that the auditor's reputation and investment opportunity set have a negative and significant effect on audit report lag. The complexity of the company's operations has no significant effect on audit report lag.